Registered nurses’ attitude and willingness to precept nursing students in Jamaica - Roper Carty MSN, Michelle; LM Lindo PhD, Jascinth; Stennett MPH, Rosain (International Journal of Advanced Nursing Studies, 2019)
Background: Registered nurses’ willingness to precept nursing students is an important factor in ensuring a positive clinical learning environment. However, in resource poor settings with high patient to nurse ratio and other challenges in the delivery of nursing care preceptorship may represent an additional challenge.Aim: To determine the willingness of registered nurses to precept student nurses in Jamaica; their attitude towards the paired preceptorship model and factors which may influence the precepting process.Design: This descriptive cross-sectional study utilized a 32-item self-administered questionnaire to collect data from 76 full-time registered nurses assigned to medical/surgical wards at a major teaching hospital.Results: Nurses had a positive attitude towards precepting (97%) and believed their actions and attitudes positively influenced the learning outcomes of students. Two-thirds of registered nurses (63%) were willing to precept students and 87% preferred the paired preceptorship model. Self-efficacy (p<0.05) best explained their willingness to participate in both paired preceptorship and clinical teaching associate models while, normative beliefs regarding clinical learning environment was significant predictor of overall willingness.Conclusion: Registered nurses studied displayed positive attitude towards preceptorship and were willing to precept students. Policy makers should note that the paired preceptorship model was favoured by the group and that personal satisfaction and professional development were motivating factors for nurses’ willingness to precept students. Formal training opportunities are needed to enhance students’ clinical learning experience. Keywords: Precept; Willingness; Registered Nurses; Student Nurses; Jamaica.